Chrysin Protects against Focal Cerebral Ischemia/Reperfusion Injury in Mice through Attenuation of Oxidative Stress and Inflammation - Yao, Yang (Int J Mol Sci, 2014)
Inflammation and oxidative stress play an important part in the pathogenesis of focal cerebral ischemia/reperfusion (I/R) injury, resulting in neuronal death. The signaling pathways involved and the underlying mechanisms of these events are not fully understood. Chrysin, which is a naturally occurring flavonoid, exhibits various biological activities. In this study, we investigated the neuroprotective properties of chrysin in a mouse model of middle cerebral artery occlusion (MCAO). To this end, male C57/BL6 mice were pretreated with chrysin once a day for seven days and were then subjected to 1 h of middle cerebral artery occlusion followed by reperfusion for 24 h. Our data show that chrysin successfully decreased neurological deficit scores and infarct volumes, compared with the vehicle group. The increases in glial cell numbers and proinflammatory cytokine secretion usually caused by ischemia/reperfusion were significantly ameliorated by chrysin pretreatment. Moreover, chrysin also inhibited the MCAO-induced up-regulation of nuclear factor-kappa B (NF-κB), cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS), compared with the vehicle. These results suggest that chrysin could be a potential prophylactic agent for cerebral ischemia/reperfusion (I/R) injury mediated by its anti-inflammatory and anti-oxidative effects.